Encyclopaedia of educational psychology # Encyclopaedia of educational psychology, Vol.5 Advanced educational psychology Vol.1 - Nayak, Ramesh K.; Chawla, Ganesh Kumar (New Delhi Arpan Publishing, 2013)
Meaning of sports psychology